Rethinking Applied Economics by Classic Grounded Theory: - Olavur Christiansen (Grounded Theory Review: An International Journal, 2017)
The heading of this paper refers to an issue that so far remains unaddressed by classic grounded theory (CGT) researchers. The aim of this paper is to take a closer look at the accordance between the CGT methodology and the field of applied economics (economic policy-making).